Transformation of arsenic species by diverse endophytic bacteria of rice roots. (15th September 2022) - Chen, Chuan; Yang, Baoyun; Gao, Axiang; Yu, Yu; Zhao, Fang-Jie
Abstract: Rice growing in flooded paddy soil often accumulates considerable levels of inorganic and organic arsenic (As) species, which may cause toxicity to plants and/or pose a risk to human health. The bioavailability and toxicity of As in soil depends on its chemical species, which undergo multiple transformations driven primarily by soil microbes. However, the role of endophytes inside rice roots in As species transformation remains largely unknown. We quantified the abundances of microbial functional genes involved in As transformation in the endosphere and rhizosphere of rice roots growing in three paddy soils in a pot experiment. We also isolated 46 different bacterial endophytes and tested their abilities to transform various As species. The absolute abundances of the arsenate reductase gene arsC and the dissimilatory arsenate reductase gene arrA in the endosphere were comparable to those in the rhizosphere, whereas the absolute abundances of the arsenite methylation gene arsM and arsenite oxidation gene aioA in the endosphere were lower. After normalization based on the bacterial 16S rRNA gene, all four As transformation genes showed higher relative abundances in the endosphere than in the rhizosphere. Consistent with the functional gene data, all of the 30 aerobic endophytic isolates were able to reduce arsenate, but only 3 strains could oxidize arsenite. Among the 16 anaerobic endophytic isolates, 4 strains belonging to Desulfovibrio, Terrisporobacter or Clostridium could methylate arsenite and/or methylarsenite. Six strains of aerobic endophytes could demethylate methylarsenite, among which three strains also could reduce and demethylate methylarsenate. None of the isolates could demethylate dimethylarsenate. These results suggest that diverse endophytes living inside rice roots could participate in As species transformation and affect As accumulation and species distribution in rice plants. Graphical abstract: Image 1 Highlights: Microbial arsenic transformation genes were detected inside the rice root endosphere. Endophytes isolated from rice roots were able to transform different As species. Microbial arsenate reduction was prevalent among aerobic endophytes. Four anaerobic endophytes were able to methylate arsenite or methylarsenite.